Measurements of Carotid Intima-Media Thickness and of Interadventitia Common Carotid Diameter Improve Prediction of Cardiovascular Events: Results of the IMPROVE (Carotid Intima Media Thickness [IMT] and IMT-Progression as Predictors of Vascular Events in a High Risk European Population) Study - BALDASSARRE, Damiano; HAMSTEN, Anders; GROSSI, Enzo; PAOLETTI, Rodolfo; TREMOLI, Elena; VEGLIA, Fabrizio; DE FAIRE, Ulf; HUMPHRIES, Steve E; SMIT, Andries J; GIRAL, Philippe; KURL, Sudhir; RAURAMAA, Rainer; et al. (Journal of the American College of Cardiology, 2012)
The goal of this study was to compare the performance of several measures of carotid intima-media thickness (C-IMT) as predictors of cardiovascular events (CVEs), and to investigate whether they add to the predictive accuracy of Framingham risk factors (FRFs). Various markers of subclinical atherosclerosis have been identified as predictors of CVEs, but the most powerful variable is still under debate. A cohort study was carried out in 5 European countries. A total of 3,703 subjects (median age 64.4 years; 48% men) were followed-up for a median of 36.2 months, and 215 suffered a first CVE (incidence: 19.9/1,000 person-years). All measures of C-IMT and the interadventitia common carotid artery diameter (ICCAD) were associated with the risk of CVEs, after adjustment for FRFs and therapies (all p < 0.005). The average of 8 maximal IMT measurements (IMT(mean-max)), alone or combined with ICCAD, classified events and non-events better than the common carotid mean IMT (net reclassification improvement [NRI]: +11.6% and +19.9%, respectively; both p < 0.01). Compared with classification based on FRFs alone, the NRI resulting from the combination of FRFs+ICCAD+IMT(mean-max) was +12.1% (p < 0.01). The presence of at least 1 plaque (maximum IMT >1.5 mm) performed significantly worse than composite IMTs that incorporated plaques (p < 0.001). Adjusted Kaplan-Meier curves showed that individuals with a FRS = 22.6% (cohort average), and both IMT(mean-max) and ICCAD above the median, had a 6.5% risk to develop a CVE over 3 years versus a 3.4% risk for those with the same FRS, and both IMT(mean-max) and ICCAD below the median. A risk stratification strategy based on C-IMT and ICCAD as an adjunct to FRFs is a rational approach to prevention of cardiovascular disease.